Strategi Pemasaran Inovatif Bagi Wirausaha di Era Digital - Mansur, Agung Hidayat; Ramayani, Indah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Digital marketing strategies play an important role in shaping entrepreneurial success in the dynamic landscape of the digital age. This research aims to find out innovative marketing strategies that can be used by entrepreneurs in the digital era. This research uses bibliometric analysis to systematically explore and synthesize the existing literature on digital marketing strategies and entrepreneurial success. Scopus' various databases are used to compile a comprehensive dataset of peer-reviewed articles published between 1993 and 2023. The analysis includes descriptive statistics, co-authorship networks, citation patterns, and keyword co-emergence, with particular emphasis on the intersection between digital marketing and entrepreneurial success. Key findings include prominent authors and their influential works, thematic groups, and the distribution of terms in the literature. Important themes explored include digital entrepreneurship, the digital economy, entrepreneurship education, and the transformative impact of digital technology on the entrepreneurial ecosystem. This research contributes to a nuanced understanding of the current state of knowledge in the field and identifies gaps and opportunities for future research. The insights gained from this analysis can inform academics and practitioners in optimizing digital marketing strategies for entrepreneurial success in the contemporary digital landscape